Musawah Movement’s Activism for Women’s Rights as Strengthening the Trend of Islamic Feminism - Dworska, Żaklina (Chrześcijaństwo-Świat-Polityka, 2024)
The article addresses contemporary discussions of gender equality in Muslim communities, where Islamic feminism has emerged as a movement that does not reject the core values of Islam and its doctrine but attempts to reread the Quran from a women’s perspective. This paper situates Islamic feminism and the activities of Musawah, an NGO focused on reinterpreting Islam, promoting approaches that address contemporary challenges to gender equality and debates about the role of religion within the context of Muslim family law. The critical approach of Islamic feminism is to resist the abuse of religious interpretation to maintain patriarchal structures while rejecting Western and secularized understandings of human rights. Based on the context of this dispute, this article analyses source documents illustrating the activities of the equality movement, which seeks to achieve its statutory goals and reform Muslim family law.